TAHAP BERPIKIR GEOMETRIS DALAM MATERI SEGITIGA DAN SEGIEMPAT DIKAJI DARI GAYA KOGNITIF DI SMP - Valeria Fransiska; Sugiatno Sugiatno; Bistari Bistari (Universitas Tanjungpura, 2019)
AbstractThe aim of this research is to find out the geometrical thinking stage of junior high school students in the material of triangle and quadrilateral based on the field dependent and field independent model of cognitive style. It needs to be clarifed that the main aspect of this research is student’s geometrical thinking stage based on the cognitive style. The research method used is descriptive method in the from of case study research. The subjects of this research are students in the class VII A of SMP Negeri 11 Pontianak. Based on the result, it showed that the students with field dependent model of cognitive style in the class is particulary in stage 1 a.k.a analysis stage. It explained that student’s thinking stage had reached the understanding to the problems corresponding with the properties of geometrical figures. Meanwhile the students with field independent model of cognitive style is particularly in stage 0 a.k.a visualization stage. This showed that in triangle and quadrilateral materials, students can only identifying, denoting, comparing, and operating the geometrical figures.Keywords: Cognitive Style, Thinking Stage.